Polymorphisms of the renin–angiotensin system are associated with blood pressure, atherosclerosis and cerebral white matter pathology. Issue 10 (12th January 2007) - van Rijn, M J E; Bos, M J; Isaacs, A; Yazdanpanah, M; Arias-Vásquez, A; Stricker, B H Ch; Klungel, O H; Oostra, B A; Koudstaal, P J; Witteman, J C; Hofman, A; Breteler, M M B; et al.
Abstract : Background: The renin–angiotensin system is involved in the development of hypertension, atherosclerosis and cardiovascular disease. We studied the association between the M235T polymorphism of the angiotensinogen gene ( AGT ) and the C573T polymorphism of the angiotensin II type 1 receptor ( AT1R ) and blood pressure, carotid atherosclerosis and cerebrovascular disease. Methods: We genotyped over 6000 subjects from the Rotterdam Study and more than 1000 subjects from the Rotterdam Scan Study. We used logistic regression and univariate analyses, adjusting for age and sex with, for AGT, the MM and, for AT1R, the TT genotype as reference. Results: We found that AGT −235T increased systolic (p for trend = 0.03) and diastolic blood pressure (p for trend = 0.04). The prevalence of carotid plaques was increased 1.25-fold (95% CI 1.02–1.52) in AGT -TT carriers. There was a significant increase in mean volume deep subcortical white matter lesions (WML) for AGT -TT carriers (1.78 ml vs 1.09 ml in the reference group; p = 0.008). A significant interaction was found between AGT and AT1R, further increasing the effect on periventricular and subtotal WML (p for interaction = 0.02). We found a non-significant increased risk of silent brain infarction for AGT -TT carriers and AT1R -CC carriers, but no effect on stroke. Conclusion: We found an association between AGT and blood pressure, atherosclerosis and WML. Also, we found synergistic effects between AGT and AT1R on the development of WML. These findings raise the question of whether the renin–angiotensin system may be a therapeutic target for the prevention of cerebral white matter pathology.